Intrastate Variations in Rural Cancer Risk and Incidence: An Illinois Case Study. Issue 5 (September 2016) - Zahnd, Whitney E.; Mueller, Georgia S.; Fogleman, Amanda J.; Jenkins, Wiley D.
Abstract : Context: Although rural-urban cancer disparities have been explored with some depth, disparities within seemingly homogeneous rural areas have received limited attention. However, exploration of intrarural cancer incidence may have important public health implications for risk assessment, cancer control, and resource allocation. Objective: The objective of this study was to explore intrastate rural cancer risk and incidence differences within Illinois. Design: Illinois's 83 rural counties were categorized into northern, central, and southern regions (IL-N, IL-C, and IL-S, respectively). Chi-square test for independence and analysis of variance calculations were performed to assess regional differences in demographic characteristics, socioeconomic deprivation, smoking history, obesity, cancer-screening adherence, and density of general practitioners. Age-adjusted incidence rates were calculated for 5 cancer categories: all cancers combined, lung, colorectal, breast (female), and prostate cancers. Unadjusted and adjusted incidence rate ratios (IRRs) were calculated to evaluate regional differences in rates for each cancer category. Results: Socioeconomic deprivation varied by region: 4.5%, 6.9%, and 40.6% of IL-N, IL-C, and IL-S counties, respectively ( P < .001). Smoking history also significantly differed by region. Mean former/current smoking prevalence in IL-N, IL-C, and IL-S counties was 46.4%, 48.2%, and 51.4%, respectively ( P = .006). In unadjusted analysis, IL-C (IRR = 1.12; 95% confidence interval [CI], 1.02-1.23) and IL-S (IRR = 1.24; 95% CI, 1.13-1.35) had increased lung cancer incidence compared with IL-N. Elevated risk remained in IL-S after adjusting for relevant factors such as smoking and socioeconomic deprivation (IRR = 1.14; 95% CI, 1.04-1.26). Conclusions: Socioeconomic deprivation, health behaviors, and lung cancer incidence varied across rural regions. Our findings underscore the importance of identifying cancer risk heterogeneity, even within a state, to effectively target risk factor reduction and cancer control interventions. Abstract : This research brief report explores intrastate rural cancer risk and incidence differences within Illinois.